ANALISIS TINGKAT KELELAHAN KERJA DAN RESIKO KELUHAN SISTEM MUSKULOSKELETAL PADA MANUAL HANDLING PRODUKSI BATU BATA DI KECAMATAN UKUI KABUPATEN PELALAWAN - ,Sharnuke Asrilsyak, Rail Agustio ,Iwan Nauli Daulay (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
Musculoskeletal Disorder is an occupational health problem that often causes major disability among workers. The occurrence of Musculoskeletal Disorder is one of the main reasons for being absent from work and results in losses for institutions that employ both loss of time, services, and materials. Red brick factory workers found several working conditions that have the potential to be risk factors for the emergence of musculoskeletal complaints, such as lifting and carrying activities, nutritional intake, work position, and working conditions. Conditions of working time show that red brick factory workers often take long breaks but once rather than short but frequent breaks, and the rest time taken by workers is usually less than 30 minutes. In addition, the piecework system and the absence of a week's rest except for religious holidays, also affect the emergence of musculoskeletal complaints. Given the important role of musculoskeletal complaints in red brick factory workers, it is necessary to study the prevalence of musculoskeletal complaints. This prevalence study was conducted to determine the magnitude of muculoskeletal complaints in brick factory workers. The research method used is a quantitative method. Methods of data collection using questionnaires, interviews and documentation. The data analysis technique used in this research is descriptive analysis technique. The results showed that in general, based on the score obtained from the results of the Work Fatigue Level variable, it was in the High category with a percentage of 49.57, so immediate action was needed. Meanwhile, the employee's Musculoskeletal System Complaint Risk data is in the high category with a percentage of 41.94, so immediate action is needed. Keywords: Musculoskeletal Disorder, Manual Handling, Work Fatigue